Synthesis of New Derivatives of BEDT-TTF: Installation of Alkyl, Ethynyl, and Metal-Binding Side Chains and Formation of Tris(BEDT-TTF) Systems - Songjie Yang; Matteo Zecchini; Andrew C. Brooks; Sara J. Krivickas; Desiree M. Dalligos; Anna M. Matuszek; Emma L. Stares; Melanie Pilkington; John D. Wallis (Magnetochemistry, 2021)
The syntheses of new BEDT-TTF derivatives are described. These comprise BEDT-TTF with one ethynyl group (HC≡C-), with two (n-heptyl) or four (n-butyl) alkyl side chains, with two trans acetal (-CH(OMe)2) groups, with two trans aminomethyl (-CH2NH2) groups, and with an iminodiacetate (-CH2N(CH2CO2−)2 side chain. Three transition metal salts have been prepared from the latter donor, and their magnetic properties are reported. Three tris-donor systems are reported bearing three BEDT-TTF derivatives with ester links to a core derived from benzene-1,3,5-tricarboxylic acid. The stereochemistry and molecular structure of the donors are discussed. X-ray crystal structures of two BEDT-TTF donors are reported: one with two CH(OMe)2 groups and with one a -CH2N(CH2CO2Me)2 side chain.